Laser Induced Thin Film Production (LITFP) Using Nitrogen (N2) Laser Deposition - Syamsir Dewang (Jurnal ILMU DASAR, 2009)
Laser induced thin film production (LITFP) technique was employed for making Lead (Pb) thin film by nitrogen laser ablation in miniature scale. The energy of nitrogen laser operated at 12.5 kv, 90 torr was 3.5 mJ with 5 ns pulse duration, thus producing peak power at around 0.7 MW. Pb plasma of 1 cm diameter was generated in each laser bombardment, producing thin film above the glass substrate. The thin film characteristics were measured by the thickness and surface morphology using scanning electron microscope (SEM). It was proved that there was a linear relationship between the number of laser shots and film thickness.